Money, Trade and Investment - Cole, G. D. H. (London : Cassell, 1954)
The book is based on a book titled 'money, its present and future, published in 1944 and in revised form in 1945 and 1947. It deals with trade and investment almost as much as with money, though it does not attempt to formulate and general theory dealing with either.
Based on the author's Money, its present and future.
423P.
osc 26/04/17
Loans
Keywords: Money; Currency question; Foreign exchange; Investments, Foreign